Corrosion behavior of X65 carbon steel in simulated oilfield produced water. Issue 4 (12th March 2014) - Zhang, Y. L.; Du, M.; Zhang, J.; Du, J. Q.
<x xml:space="preserve">Abstract</x> Corrosion behavior of X65 steel in simulated oilfield water was studied by weight loss, polarization curve, electrochemical impedance spectroscopy, scanning electron microscope, and X‐ray diffraction methods. Effects of temperature, acetic acid concentration, and CO2 partial pressure on the corrosion behavior were discussed. Results showed that the corrosion rate increased with the increasing of temperature, acetic acid concentration, and CO2 partial pressure. High temperature favored the formation of FeCO3; the addition of acetic acid could speed hydrogen depolarization, but the more acetic acid could remove FeCO3 layer, CO2 mainly influenced the cathodic reaction, appearing limiting diffusive current density. Acetic acid and CO2 had a synergistic effect on the corrosion process of X65 carbon steel in simulated oilfield produced water.